2015
DOI: 10.1021/acscombsci.5b00046
|View full text |Cite
|
Sign up to set email alerts
|

Mannich Bases as Enone Precursors for Water-Mediated Efficient Synthesis of 2,3,6-Trisubstituted Pyridines and 5,6,7,8-Tetrahydroquinolines

Abstract: A highly efficient, regioselective and environmentally-friendly method has been developed for water mediated synthesis of 2,3,6-trisubstituted pyridines and 5,6,7,8-tetrahydroquinolines. The introduced method allows easy preparation of various polysubstituted pyridines and 5,6,7,8-tetrahydroquinolines via domino reaction of an enolizable ketone, ammonia and enones derived from different Mannich bases in mild reaction conditions. Montmorillonite K-10 promoted this one-pot three-component reaction and gave both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…A highly efficient water-mediated, three-component reaction was developed for the synthesis of polysubstituted pyridines and 5,6,7,8-tetrahydroquinolines. As shown in Scheme , the reaction between enolizable ketones 1439 , Mannich bases 1440 , and ammonium acetate afforded 5,6,7,8-tetrahydroquinolines 1441 in the presence of montmorillonite K-10 in water at 80 °C, in high yields (up to 96%) . Enone A , generated in situ from Mannich bases 1440 , and enamine B , arising form ketone 1439 and ammonium acetate, are the key intermediates for the formation of the target compounds.…”
Section: Synthesis Of Tetrahydroquinolines With Other Hydrogenation P...mentioning
confidence: 99%
See 1 more Smart Citation
“…A highly efficient water-mediated, three-component reaction was developed for the synthesis of polysubstituted pyridines and 5,6,7,8-tetrahydroquinolines. As shown in Scheme , the reaction between enolizable ketones 1439 , Mannich bases 1440 , and ammonium acetate afforded 5,6,7,8-tetrahydroquinolines 1441 in the presence of montmorillonite K-10 in water at 80 °C, in high yields (up to 96%) . Enone A , generated in situ from Mannich bases 1440 , and enamine B , arising form ketone 1439 and ammonium acetate, are the key intermediates for the formation of the target compounds.…”
Section: Synthesis Of Tetrahydroquinolines With Other Hydrogenation P...mentioning
confidence: 99%
“…Mannich bases 1440, and ammonium acetate afforded 5,6,7,8-tetrahydroquinolines 1441 in the presence of montmorillonite K-10 in water at 80 °C, in high yields (up to 96%) 608. Enone A, generated in situ from Mannich bases 1440, and enamine B, arising form ketone 1439 and ammonium acetate, are the key intermediates for the formation of the target compounds.Shang, Song, and co-workers developed a Yb(OTf) 3catalyzed four-component reaction for the synthesis of antimicrobial 5,6,7,8-tetrahydroquinolines (Scheme 392) 609.…”
mentioning
confidence: 99%
“…Vinyl ketones are generally unstable and high-cost starting materials; therefore, we previously used Mannich bases as enone precursors. 21 Here, our strategy began with the reaction of 1 H -indole (3) with Mannich base 1a in water (Scheme 2). The reaction furnished target molecule 4a with quite a high yield (50%) under catalyst-free conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Hanashalshahaby and Unaleroglue [ 66 ] showed that pyridine-3-phosphonates 10 can be obtained by three-component oxidative coupling of diethyl (2-oxobutyl)phosphonate ( 8 ) with Mannich bases 9 and ammonium acetate ( 1 ) in the presence of catalyst K-10 ( Scheme 2 ). The product yields are reasonable both for aryl- and alkyl-substituted Mannich bases.…”
Section: Pyridinesmentioning
confidence: 99%